PELATIHAN PEMBUATAN BRIKET DARI “LIMBAH KULIT DURIAN “ - Anggraini, Yussi; Herwono, Bagiyo; Hardiana, Maulidia Tifani Alfin Nur; Surya, Maulidina Rahmawati; Prasetyo, Hodi Eko (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
In the implementation of the PKM (community service) program, it is in the form of using durian skin raw materials to be used as battery material. This training was addressed to PKK women ds. Panemon sugihwaras Bojonegoro. This workshop aims to provide knowledge and training to PKK women that the waste used for cooking can be useful. The output targets of this community service program are 1) training on making briquettes/batteries from durian skin 2) knowledge about renewable energy related to waste in daily life and 3) scientific publications. The method used in this activity uses an informal discussion between individuals and PKK groups. In this activity, information was extracted about PKK activities that have been implemented and have not been implemented in order to find out how far the existing programs in the village are. These results are used as the preparation of initial information as PKM data. The result of this PKM activity is the practice of making briquettes for PKK mothers in utilizing durian skin waste. The conclusion of this activity is to increase the knowledge and skills of PKK mothers for an activity to utilize existing waste in the village environment. Keywords: Renewable energy, durian peel, battery